2001
DOI: 10.1073/pnas.98.4.1958
|View full text |Cite
|
Sign up to set email alerts
|

Female preproenkephalin-knockout mice display altered emotional responses

Abstract: The endogenous opioid system has been implicated in sexual behavior, palatable intake, fear, and anxiety. The present study examined whether ovariectomized female transgenic preproenkephalin-knockout (PPEKO) mice and their wild-type and heterozygous controls displayed alterations in fear and anxiety paradigms, sucrose intake, and lordotic behavior. To examine stability of responding, three squads of the genotypes were tested across seasons over a 20-month period. In a fear-conditioning paradigm, PPEKO mice sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(44 citation statements)
references
References 24 publications
(8 reference statements)
3
41
0
Order By: Relevance
“…In this regard, it has been suggested that progesterone may induce opposite effects to those of estradiol on both -opioid receptor binding and in the capacity to release endogenous opioids activating those receptors (Ratka et al, 1991;Shen et al, 1995;Ragnauth et al, 2001;Sinchak and Micevych, 2001;Mills et al, 2004). Additional investigation into these processes appears necessary in view of the results obtained here.…”
Section: Discussionmentioning
confidence: 72%
“…In this regard, it has been suggested that progesterone may induce opposite effects to those of estradiol on both -opioid receptor binding and in the capacity to release endogenous opioids activating those receptors (Ratka et al, 1991;Shen et al, 1995;Ragnauth et al, 2001;Sinchak and Micevych, 2001;Mills et al, 2004). Additional investigation into these processes appears necessary in view of the results obtained here.…”
Section: Discussionmentioning
confidence: 72%
“…In a previous study, it was shown that CRF, when delivered into the GP, induces the release of enkephalin (Sirinathsinghji et al, 1989), an anxiolytic endogenous opioid (König et al, 1996;Kang et al, 2000;Ragnauth et al, 2001) that is released in the GPe by afferent neurons in the striatum. Based on these results, we suggest a mechanism in which reduced CRFR1 expression increases anxiety-like behavior in part by affecting enkephalin release.…”
Section: Discussionmentioning
confidence: 99%
“…This discovery is of crucial importance from a physiological and physiopathological point of view when the extent of the functions mediated by the endogenous opioidergic pathways are considered. Indeed, the endogenous opioid peptides, in particular the enkephalins, have a pivotal role in the control of pain perception and mood-related states, including modulation of emotional and͞or motivational responses (5,6,19). Endogenous Opiorphin could facilitate adaptative responses to threat-inducing stimuli by potentiating analgesic and antidepressive-like behavior, induced by endogenous enkephalinergic systems, in humans.…”
Section: Human Opiorphin Is a Dual Inhibitor Of Enkephalin-degrading mentioning
confidence: 99%